2000
DOI: 10.1785/0119990070
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Phase-Detection and Identification by Full Use of a Single Three-Component Broadband Seismogram

Abstract: Automatic-time picking continues to be a significant issue in seismogram analysis. Any individual method is based on separation of signal and noise in a particular domain and cannot ensure consistent onset time picking under all source, receiver, path, and noise conditions. However, a combination of three methods based on differing aspects of seismograms can be used to provide automated and consistent phase detection and interpretation using a single three-component record. For arrival detection, a combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(32 citation statements)
references
References 14 publications
0
30
0
2
Order By: Relevance
“…Although this method avoids already some of the misinterpretation, it still fails for a large number of Sn phases. A possible future approach could include an AR-modeling window, moving from the noise part toward the expected Sn signal as proposed, for example, by Bai and Kennett (2000). The onset of a seismic signal is then characterized by increased order and values of the AR coefficients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this method avoids already some of the misinterpretation, it still fails for a large number of Sn phases. A possible future approach could include an AR-modeling window, moving from the noise part toward the expected Sn signal as proposed, for example, by Bai and Kennett (2000). The onset of a seismic signal is then characterized by increased order and values of the AR coefficients.…”
Section: Discussionmentioning
confidence: 99%
“…They use a pattern recognition technique to identify and pick S waves. A similar combined approach is used by Bai and Kennett (2000) to detect and identify regional P and S phases in 3C seismograms. They implement a polarization analysis based on complex traces derived from the Hilbert transform of the real part of the signal.…”
Section: Introductionmentioning
confidence: 99%
“…With this method, the results are still affected by the length of the time window and the shape of the waveform. In other studies that identified the first arrival of seismic waveforms (Zhang et al 2003, Bai and Kennett 2000, Liu et al 2013, large deviations exist between the real arrivals and the P-wave picking results (Dai and MacBeth 1995).…”
Section: Introductionmentioning
confidence: 91%
“…Other methods for seismic phase detection and picking are based on neural network analysis, polarization analysis, frequency analysis, and other approaches (e.g., Magotra 1987;Cichowicz 1993;Bai and Kennett 2000).…”
Section: Automatic Detection and Picking Algorithmsmentioning
confidence: 99%